2012
DOI: 10.1021/jm3015519
|View full text |Cite
|
Sign up to set email alerts
|

Phenyltetrahydroisoquinoline–Pyridinaldoxime Conjugates as Efficient Uncharged Reactivators for the Dephosphylation of Inhibited Human Acetylcholinesterase

Abstract: Pyridinium and bis-pyridinium aldoximes are used as antidotes to reactivate acetylcholinesterase (AChE) inhibited by organophosphorus nerve agents. Herein, we described a series of nine nonquaternary phenyltetrahydroisoquinoline-pyridinaldoxime conjugates more efficient than or as efficient as pyridinium oximes to reactivate VX-, tabun- and ethyl paraoxon-inhibited human AChE. This study explores the structure-activity relationships of this new family of reactivators and shows that 1b-d are uncharged hAChE rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…For conjugate 3, our results are in line with what Mercey et al had reported, but they did not evaluate the reactivation ability against sarin-inhibited hAChE. 24,25 In contrast to those quaternary oximes, 7g, 7h and 3 emerged as more broad-spectrum for sarin-, VX-and tubaninhibited hAChE, while obidoxime and TMB-4 were less efficient for sarin; HI-6 and MMB-4 were much less efficient for tabun poisoning. We also determined the reactivation potency of imidazolium-2-aldoxime (5b), the results demonstrated that most conjugates showed improved reactivation potency, especially in the cases of 7d, 7g and 7h, which justified the concept of dual-site biding strategy.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…For conjugate 3, our results are in line with what Mercey et al had reported, but they did not evaluate the reactivation ability against sarin-inhibited hAChE. 24,25 In contrast to those quaternary oximes, 7g, 7h and 3 emerged as more broad-spectrum for sarin-, VX-and tubaninhibited hAChE, while obidoxime and TMB-4 were less efficient for sarin; HI-6 and MMB-4 were much less efficient for tabun poisoning. We also determined the reactivation potency of imidazolium-2-aldoxime (5b), the results demonstrated that most conjugates showed improved reactivation potency, especially in the cases of 7d, 7g and 7h, which justified the concept of dual-site biding strategy.…”
supporting
confidence: 90%
“…But all these conjugates are pyridyl aldoximes and they are difficult to prepare due to a long synthetic route, moreover, their reactivation potencies against sarin-inhibited hAChE are still unknown. [24][25][26][27] Hence we sought to develop alternatives of the pyridyl aldoximes.…”
mentioning
confidence: 99%
“…Recently, the ability of neutral reactivator pyridinealdoxime to reactivate OP inhibited enzyme was reported [23][27]. This pyridinealdoxime showed a considerable capacity to reactivate VX-, tabun- and ethyl paraoxan inhibited human AChE [27].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, non-ionic reactivators have been synthesized, which can more easily penetrate the BBB and reactivate the inhibited h AChE [23][27]. Non-quaternary pyridinealdoxime compounds exhibited a high potency for the reactivation of VX and tabun-inhibited h AChE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation